Kesesuaian Hasil Pemeriksaan RT PCR, RDT NS1, dan RDT IgM Pasien Penyakit Dengue - Paisal Paisal; Mukhlis Zuardi; Reni Herman (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2016)
The incidence of dengue disease in the world is estimated at 390 million cases per year. In Indonesia, during 2013 there were 35-40 cases per 100.000 population, with a mortality rate of 0.73%. This study aimed to determine the suitability and the percentage of RT-PCR, RDT NS1, and RDT IgM detection examination. Samples were obtained from hospitals in Aceh province during 2012. The research samples reached 100 collected samples, it was only 82 samples that fulfill the analysis criteria. Cohen’s Kappa test result showed there was moderate suitability between RT-PCR and RDT NS1 (K=0,404, p = 0,000), and weak suitability between RT-PCR began RDT IgM (K=0,139, p = 0,046). While the percentage of detection for RT-PCR, RDT NS1, dan RDT IgM were 16%, 10%, and 60%. RDT IgM is the best alternative for laboratory examination in the hospital.